Design and experiment of spiral conveying pipe in pneumatic centralized fertilizer discharge system. - Longmei Zhang; Wensheng Yuan; Yugang Feng; Chengqian Jin; Gangwei Liu; Shuangcheng Xie (PLoS ONE)
To address the problem of poor fertilizer uniformity caused by vibration and skewing during rice transplanter operations, this study developed a pneumatic centralized spiral fertilizer discharge system. By leveraging the combined effects of high-speed swirling airflow and a spiral conveying pipe, the system generates a high-speed rotating air-fertilizer mixed flow, mitigating the negative effects of ground unevenness and machine vibration on fertilizer performance. Through multi-parameter coupled simulation experiments, the optimal working parameters for the spiral conveying pipe were identified as follows: a spiral pipe length of 444.35 mm, a cross-sectional slope angle of 26°, an airflow velocity of 35 m s-1, and a screw pitch of 105 mm, achieving a coefficient of variation of 4.61%. To simulate complex field environments, comparative bench experiments were conducted between the spiral conveying pipe and the smooth straight pipe. The results showed that, at inclination angles of 0°, 5°, 10°, and 15°, the coefficients of variation for the spiral conveying pipe were 4.53%, 5.87%, 8.47%, and 9.64%, respectively, significantly outperforming the smooth straight pipe. Compared to the smooth straight pipe, the spiral conveying pipe reduced the coefficients of variation by 50.81%, 54.07%, 44.53%, and 50.54%, respectively. Field experiments demonstrated that the coefficient of variation for the spiral conveying pipe was 5.27%, representing a 63.1% reduction compared to the 14.28% recorded for the smooth straight pipe. The results confirm the effectiveness of the spiral conveying pipe's structural design and its superior fertilizer performance, making it highly suitable for complex paddy field environments.